Development of a monoclonal antibody‐based antigen capture enzyme‐linked immunosorbent assay for detection of H7N9 subtype avian influenza virus. Issue 6 (27th July 2020) - Yang, Fan; Xiao, Yixin; Liu, Fumin; Yao, Hangping; Wu, Nanping; Wu, Haibo
Abstract: To establish a rapid detection method for H7N9 avian influenza virus (AIV), monoclonal antibodies (mAbs) against hemagglutinin (HA) of H7N9 were developed to establish an antigen‐capture enzyme‐linked immunosorbent assay (AC‐ELISA). AC‐ELISA achieved high specificity and sensitivity, with a detection limit of 3.9 ng/mL for H7N9 HA protein (A/Zhejiang/DTID‐ZJU01/2013), and 2 −2 HA unit/100 μL for live H7N9 AIV. The inter‐ and intra‐assay coefficient of variation was less than 10%. Compared with conventional virus isolation detection, the sensitivity and specificity were 94.96% and 88.24%, respectively. AC‐ELISA proved to be a rapid and practical technique for the detection of H7N9 AIV. Highlights: 1. An AC‐ELISA was developed by two specific monoclonal antibodies. 2. The AC‐ELISA achieved high specificity and sensitivity, with a detection limit of 3.9 ng/mL for H7N9 HA protein. 3. Compared with virus isolation detection, the sensitivity and specificity were 94.96% and 88.24%, respectively.